Research on Status Monitoring and Fault Alarm Device of Drop-out Fuse. Issue 3 (June 2021) - Ju, Zeli; Xing, Wei; Duan, Wei; Sun, Haofei; Sun, Xin; Liu, Shulin
Abstract: Drop-out fuse is a common circuit protection device. When a short fault occurs in the circuit, the fusion pipe will drop and the fuse will be disconnected, so as to isolate the fault line. However, in practical application, there is no reliable means and device for remote monitoring, resulting in the failure information can not be found in time. Although the traditional drop-out fuse alarm device can play the role of fault alarm. It has the disadvantages of large time difference and high cost. Based on this, a set of status monitoring and alarm device according to the drop characteristics of drop-out fuse after failure has been developed. The inclination and temperature of the fusion pipe are monitored by sensors in real time, and the data is sent to the master station through wireless communication. When a fault occurs, the operation and maintenance staff can be notified in time to repair the fault point. Through experimental demonstration, it can be concluded that the fuse status monitoring and fault alarm device has stable performance, convenient control and high cost performance. If it is applied to the distribution network, it can shorten the outage time, reduce economic losses and increase user satisfaction.